Quantitative Analysis of Soil Erosion Along Yangtze River in Jiangsu Province Based on Geographic Detector - Wu Zhenyu; Luo Mengqi; Guo Hongli; Wu Fang; Huang Yunan; Dai Yuting; Liu Xia (Shuitu baochi tongbao, 2022)
[Objective] The spatial distribution characteristics of soil erosion was explored, the main influencing factors were identified and quantitative attribution of driving force factors were carried out, in order to guide regional soil erosion control and ecological environment construction. [Methods] Taking the area along the Yangtze River in Jiangsu Province as the research object, based on high-resolution remote sensing images, digital elevation models, and long series of rainfall data, the methods of Chinese soil loess equation (CSLE) and geographic detectors were used to explore the dominant influencing factors and interactions of the spatial variability of soil erosion, to identify areas with high risk of soil erosion. [Results] ① Slope and land use types dominated soil erosion in plain and hilly areas. The soil erosion of tea gardens was dominated by vegetation coverage, and soil erosion of other types of land use was dominated by slope. ② The dominant interaction of soil erosion was slope superimposition of land use types. The dominant interaction factors between tea garden and grassland were slope and vegetation coverage, and the dominant interaction factors for soil erosion of other types were slope and rainfall. ③ High-risk areas of soil erosion in orchards, tea gardens, woodlands and areas disturbed by production and construction activities were located in hilly mountainous areas with slopes> 20°, rainfall of 1300～1 400 mm, and high vegetation coverage. [Conclusion] The geo-detector is easy to operate. The results include single factor influence, two factor interaction and risk area analysis. Close attention should be paid to the problems of soil erosion in areas disturbed by production and construction activities and garden plots in Jiangsu Province.